Intensive strength and balance training with the Kinect console (Xbox 360) in a patient with CMT1A. (17th November 2018) - Pagliano, Emanuela; Foscan, Maria; Marchi, Alessia; Corlatti, Alice; Aprile, Giorgia; Riva, Daria
ABSTRACT: Background : Effective drugs for type 1A Charcot-Marie-Tooth (CMT1A) disease are not available. Various forms of moderate exercise are beneficial, but few data are available on the effectiveness of exercise in CMT1A children. Aim : To investigate the feasibility and effectiveness of exercises to improve ankle strength and limb function in a child with CMT1A. Setting : Outpatient clinic. Population : Nine-year-old boy with CMT1A. Methods : The rehabilitation program consisted of ankle exercises and Kinect videogame-directed physical activities (using an Xbox 360 console/movement sensor) that aimed to improve balance and limb strength. The program was given 3 times a week for 5 weeks. The child was assessed at baseline, after 5 weeks, and 3 and 6 months after. Results : By the end of follow-up, child balance and endurance had improved, but ankle strength did not. Conclusions : The encouraging results for balance and endurance justify further studies on videogame-directed activities in CMT1A children/adolescents.